DNA repair proteins Metnase and PARP1 regulate DNA integration - Nie, Jingyi, author; Nickoloff, Jac A., advisor; Bailey, Susan M., committee member; Liber, Howard L., committee member; Chen, Chaoping, committee member (Colorado State University. Libraries, 2015)
DNA integration occurs naturally in various formats and plays important roles in evolution. DNA integration also affects human and animal health. Various genome-editing tools have been developed based on site-specific DNA integration. In mammalian cells, DNA integration is largely random. The mechanism of random DNA integration is not fully understood but has close association with repair of double-strand DNA damage. There are two major pathways to repair double-strand breaks (DSBs), homologous recombination (HR) and non-homologous end joining (NHEJ). In mammalian cells, NHEJ occurs more frequently than HR, possibly explains why random integration is more efficient than homology-directed integration or gene targeting. Proteins function in DSB repair pathways often engage in DNA integration. Metnase is a fusion protein that only expresses in higher primates, including humans. Metnase contains a SET methyltransferase domain and a transposase domain. Metnase promotes efficiency and accuracy of NHEJ and promotes DNA integration. The SET domain dimethylates histone H3K36 at DSB sites, and the transposase domain binds to the human Mariner transposon Hsmar1 terminal inverted repeat (TIR) sequence specifically. Both domains have been shown to be important for the role of Metnase in NHEJ. In this study, we tested the role of Metnase in promoting plasmid integration. We hypothesized that Metnase promotes plasmid integration through its functions in the NHEJ pathway. Metnase enhances the efficiency and accuracy of NHEJ, we predict that overexpression of Metnase can prevent integrating plasmid and genomic DNA at integration sites from large deletions. Besides, if the specific TIR binding of Metnase can direct more DNA integration into the TIR sequence in the human genome, overexpression of Metnase would increase the ratio of DNA integration found at or nearby TIR region. To test this hypothesis, we mapped plasmid integration in the human cell line HEK293T at low and high levels of Metnase expression. Our results demonstrated that Metnase promotes plasmid DNA integration independently of TIR sequence in the human genome. Overexpression of Metnase suppressed microhomology-mediated DNA integration, supporting our hypothesis that Metnase promotes DNA integration through classical NHEJ (cNHEJ). In contrast to cNHEJ, alternative NHEJ (aNHEJ) utilizes a different set of core proteins to rejoin broken ends. Compared to cNHEJ, aNHEJ is more error-prone and considered as the major generator of chromosomal translocations. Initiation of aNHEJ requires end resection. PARP1 plays an important role in initiating aNHEJ by recruiting end resection factors to DSBs. PARP1 has also been shown to promote DSB-induced chromosomal translocations. Based on the structural similarity between chromosomal translocations and DNA integration, we hypothesized that PARP1 may promote a sub-set of DNA integration, possibly through aNHEJ. We tested the effects of two PARP1 inhibitors PJ34 and Olaparib on DNA integration. Surprisingly, the two inhibitors showed opposite effects on DNA integration. PJ34 suppressed DNA integration, while Olaparib promoted DNA integration. We then confirmed PARP1 promoted DNA integration in a stable PARP1 knockdown cell line. Future studies are needed to understand the engagement of PARP1 in DNA integration and interpret the result where Olaparib promotes DNA integration.